Biliary tract and gallbladder biomechanical modelling with physiological and clinical elements - Li, Wenguang, 1964- (Boca Raton : CRC Press, 2021)
"Gallstone and other diseases of the biliary tract affect more than around twenty percent of the adult population. The complications of gallstones, acute pancreatitis and obstructive jaundice can be lethal. This is the first book to systematically treat biliary tract and gallbladder modelling with physiological and clinical information in biomechanical context. The book provides readers with detailed biomechanical modelling procedures for the biliary tract and gallbladder based on physiological information, clinical observations and experimental data and with the results properly interpreted in terms of clinical diagnosis and with biomechanical mechanisms for biliary diseases. The book can be used as reference book for university undergraduates, postgraduates, professional researchers in applied mathematics, biomechanics, biomechanical engineering and biomedical engineering as well as related surgery doctors"--
OCLC-licensed vendor bibliographic record.
Keywords: Biliary tract -- Physiology -- Computer simulation; Gallbladder -- Physiology -- Computer simulation; Biomechanics; MEDICAL / Biotechnology; TECHNOLOGY / General; TECHNOLOGY / Engineering / General